Best Answer

Taking the equation to be y=ax2 + bx +c , and using the formula x = -b plus/minus sqrt (b2-4ac), all over 2a: x = (-3+21)/12 or (-3-21)/12 so x = 1.5 or -2

Q: Solve 6x2 plus 3x -18 equals 0 using quadratic formula?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Solve using the quadratic formula

Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523

X= (3/5 , -2)

It can be solved by using the quadratic equation formula.

By using the quadratic equation formula

Related questions

Solve using the quadratic formula

Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523

It can be solved by using the quadratic equation formula.

X= (3/5 , -2)

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

By using the quadratic equation formula

By using the quadratic equation formula: x = -5 and x = 3

For any quadratic ax2 + bx + c = 0 we can find x by using the quadratic formulae: the quadratic formula is... [-b +- sqrt(b2 - 4(a)(c)) ] / 2a

-34

2x2-10+7 = 0 Solving the quadratic equation using the quadratic formula will give you two solutions and they are: x = (5 - the square root of 11)/2 or x = (5 + the square root of 11)/2

Using the quadratic equation formula: x = 8.42 or x = -1.42

x = 7/2 and also x = -3/2 by using the quadratic equation formula.